2019
DOI: 10.1002/admi.201801923
|View full text |Cite
|
Sign up to set email alerts
|

Operando Observations and First‐Principles Calculations of Reduced Lithium Insertion in Au‐Coated LiMn2O4

Abstract: The deposition of protective coatings on the spinel LiMn2O4 (LMO) lithium‐ion battery cathode is effective in reducing Mn dissolution from the electrode surface. Although protective coatings positively affect LMO cycle life, much remains to be understood regarding the interface formed between these coatings and LMO. Using operando powder X‐ray diffraction with Rietveld refinement, it is shown that, in comparison to bare LMO, the lattice parameter of a model Au‐coated LMO cathode is significantly reduced upon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…We propose that Li is pushed away from the external LMO surface upon TMA exposure due to electrostatic repulsion from Al 3+ incorporated into the surface of the LMO, as well as positively charged −CH 3 groups bound to surface O . This is analogous to the observation of positively charged Au coatings leading to lithium depletion at the LMO surface Figure a presents DFT + U -calculated Li vacancy formation energy vs depth into the LMO(111) surface.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…We propose that Li is pushed away from the external LMO surface upon TMA exposure due to electrostatic repulsion from Al 3+ incorporated into the surface of the LMO, as well as positively charged −CH 3 groups bound to surface O . This is analogous to the observation of positively charged Au coatings leading to lithium depletion at the LMO surface Figure a presents DFT + U -calculated Li vacancy formation energy vs depth into the LMO(111) surface.…”
mentioning
confidence: 66%
“…44 This is analogous to the observation of positively charged Au coatings leading to lithium depletion at the LMO surface. 46 Figure 5a presents DFT + U-calculated Li vacancy formation energy vs depth into the LMO(111) surface. The Li vacancy formation energy in pristine LMO (black data series in Figure 5a) is predicted to be ∼3.9 eV in the bulk and 4.4 eV at the LMO surface (depth of ∼0 Å in Figure 5a).…”
mentioning
confidence: 99%
“…These effects have been demonstrated recently, where indirect decomposition reaction pathways can lead to larger stability windows than predicted by bulk thermodynamics . Previous computational studies have analyzed the stability of solid electrolyte surface phases, and the construction of solid/solid interfacial models have been applied in previous studies of various energy storage systems. ,, In concert with experimental characterization, such computational analyses can be used to gain a more comprehensive understanding of interfacial reactivity in solid-state batteries and develop rational strategies to control it.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, X-ray photoelectron spectroscopy experiments have shown that LLTO is unstable against Li metal and cyclic voltammetry experiments indicated that LLTO undergoes a reduction reaction with lithium around 1.5–1.7 V vs Li/Li + . These material instabilities at low voltages make the Li/LLTO interface a compelling model system to understand and control aspects of solid/solid interfacial chemistry. In addition to an understanding of the bulk LLTO thermochemistry, analysis of surface and interfacial thermodynamics and metal–semiconductor band alignment ,,, can aid in forming a more comprehensive understanding of the driving forces for interfacial decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spinel LiMn 2 O 4 -based Li-ion batteries suffer from capacity fading mainly due to manganese (Mn 2+ ) ion dissolution (Hunter, 1981;Park et al, 2011), electrolyte oxidation, and the formation of Jahn-Teller distorted Li 2 Mn 2 O 4 tetragonal phases (Arora et al, 1998;Dai et al, 2013) upon cycling. It's believed that manganese dissolution is the major cause of deterioration since Jahn-Teller distortion and electrolyte oxidation can be controlled by cycling at restricted voltages (Bassett et al, 2019;Xia et al, 1997).…”
Section: Introductionmentioning
confidence: 99%